Parenting Out of Control : Anxious Parents in Uncertain Times. - Nelson, Margaret K., 1944- (NYU Press, 2010)
They go by many names: helicopter parents, hovercrafts, PFHs (Parents from Hell). The news media is filled with stories of well-intentioned parents going to ridiculous extremes to remove all obstacles from their child's path to greatness ... or at least to an ivy league school. From cradle to college, they remain intimately enmeshed in their children's lives, stifling their development and creating infantilized, spoiled, immature adults unprepared to make the decisions necessary for the real world. Or so the story goes. Drawing on a wealth of eye-opening interviews with parents across the co.